Public criminology, reflexivity and the enterprise university: Experiences of research, knowledge transfer work and co-option with police forces - Lumsden, Karen (Theoretical criminology, 2018)
This article reflects on an enterprise project which aimed to build partnerships with police forces in England. In attempting to do ‘public criminology' we had to negotiate internal and external organizational cultures, public management and ‘audit culture'. We focus on two levels of co-option we experienced during the project, by the university and the police: (1) internal university pressures such as definitions of ‘research' and ‘enterprise', funding and the terms of the ‘contract' of the project; and (2) external pressures when engaging with police that included new public management principles and ‘fast academia'. The discussion draws on data from field notes and interviews with police officers and staff.